Pelatihan Media Pembelajaran Interaktif Canva Untuk Meningkatkan Motivasi Belajar Siswa Kelas XI - Nurus Sarifatul Ngaeni; Suherno Suherno (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2026)
In today's In today’s digital era, the ability to create engaging and interactive learning media has become an essential need, particularly in supporting more effective and enjoyable teaching and learning processes. However, not all students possess the skills to use practical and easily accessible graphic design applications. Therefore, Canva Graphic Design Training activity was conducted at SMK Negeri 1 Wanayasa, involving 20 students as participants. This activity aimed to enhance students' skills in using Canva as a digital-based graphic design platform to create creative and relevant learning media. The training was carried out through lectures, demonstrations, hands-on practice, and evaluation using pre-tests and post-tests. The results showed improvement in participants' abilities in understanding basic design concepts and technical skills using Canva, as indicated by increased post-training evaluation scores. The pre-test score was 59.0, while the post-test score increased to 79.0. In addition, students were able to produce visually appealing learning media products such as posters and presentations.This activity not only provided technical skills but also encouraged students' creativity utilizing technology for educational purposes. Through this training, it can serve as an initial step in building a culture of digital literacy and the use of design technology within the school environment.